Mechanism and implementation conditions of simplified procedural form in Ukrainian legal proceeding: foreign experience borrowing - Козирєва, Валентина Петрівна; Бабенко, Олена Юріївна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2015)
This article deals with investigation of system of features of economical procedure and possibility of implementation of trial foreign experience according to the simplified procedural form by analogy with Russian Federation in economical proceeding of Ukraine. The analysis of methods is carried out with the help of which the simplified procedural form is realized; economical disputes that should be tried under simplified proceeding are characterized. This article is devoted to research of the simplified procedures of the economic rule-making in Ukraine, countries of the CIS and states of European Union. The problems of application of the simplified realization are analyzed in the aspect of optimization of the normatively-legal adjusting and perfection of practice of application of right of norms of Economic procedure code of Ukraine, regulative the judicial order of consideration of the businesses attributed to the simplified realization. In the article the existent forms of the simplified productions are analyzed and the conclusion about classification of existent forms of simplification of economic process on primary and situation simplification is grounded.